1977
DOI: 10.1099/00221287-100-1-167
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbon Dioxide on Growth and Carbohydrate Metabolism in Sclerotium rolfsii

Abstract: 2 %' (v/v) in air enhanced the growth rate and inhibited sclerotium formation in the fungus Sclerotium rolfii Sacc. A CO, concentration of 10 % inhibited growth. Similar growth patterns were observed when the fungus was grown on a medium supplemented with the fungicide carboxin, which inhibits succinate dehydrogenase. A high CO, concentration (I to 10 %) or growth on carboxin-supplemented medium caused a decrease in succinate dehydrogenase activity and significant increases in isocitrate lyase, isocitrate deh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
4
1

Year Published

1980
1980
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 16 publications
2
4
1
Order By: Relevance
“…Presumably, initiation, development and maturation of sclerotia in S . rolfsii require higher levels of energy and metabolites than the usual vegetative growth (Kritzman et al, 1977). In the present study we have detected changes in total lipid content as well as in their distribution in submerged culture.…”
Section: Discussionsupporting
confidence: 53%
“…Presumably, initiation, development and maturation of sclerotia in S . rolfsii require higher levels of energy and metabolites than the usual vegetative growth (Kritzman et al, 1977). In the present study we have detected changes in total lipid content as well as in their distribution in submerged culture.…”
Section: Discussionsupporting
confidence: 53%
“…The IDH enzyme was chosen for several reasons: (i) it catalyzes a CO 2 -producing reaction and is therefore assumed to be affected by CO 2 (22,25), (ii) it only catalyzes one reaction, (iii) the enzyme was known to exist in the organism (14,41), and (iv) an IDH kit was commercially available. The slight but significant increase in IDH activity in the presence of CO 2 and oxygen is in contrast to the findings in the gram-negative Pseudomonas aeruginosa (25) but in accordance with those in the yeast Sclerotium rolfsii (28). Although the observed differences were not statistically significant for the anaerobic cultures, the observed changes were consistent in replicate experiments (i.e., the lack of statistical significance is not the result of some positive and some negative differences), and they are therefore regarded as being trends worth noting.…”
Section: Discussioncontrasting
confidence: 53%
“…1). If their resistance is compared to that of some other organisms reported in literature, it is increased in the order: Sclerotium roljsii (Kritzman et al 1977) < Erwiniu spp. and Pseudomonus Juorescens (Wells 1974) < Ps.…”
Section: Discussionmentioning
confidence: 94%
“…At present there are two major theories for explaining the C02 inhibition of cell growth: (i) C02 inhibits enzymatic reactions critical for growth, e.g. carboxylation/decarboxylation reactions (King & Nagel 1975;Kritzman et al 1977); (ii) C o t affects the permeability of the cell membrane (Sears & Eisenberg 1961). The latter theory has been further developed in relation to spore germination (Enfors & Molin 1978b) and it has been suggested that the mechanism of C 0 2 inhibition of the germination of E. cereus spores involves a phase transition in the ge1:liquid-crystal equilibrium of the membrane lipids, resulting in an increased fluidity of the membrane.…”
Section: Discussionmentioning
confidence: 99%